NUTRITIVE REGIME OPTIMIZATION AS A FACTOR OF INCREASING CROP PRODUCTIVITY OF GRASS PEAVINE (LATHIRUS SATIVUS L.) - Yeremko, L. S.; Shvets, A. Yu.; Kobylynskyi, I. V.; Saienko, V. O. (Scientific Progress & Innovations, 2021)
One of the ways to solve the problem of protein of plant protein deficiency is to expand the species com-position and sown areas of leguminous crops, which are characterized by very high stability of grain productivity under extreme environmental conditions due to the complex effect of high temperatures and lack of productive moisture in the root layer of the soil. In this regard, grass peavine is a very promising crop. Its plants have a unique ability to enter symbiotic relationships with nodule bacteria of Rhizobium genus and accumulate molecular nitrogen in the aboveground and root biomass during the growing season in the form of protein and other nitrogen-containing organic compounds. An important agro-technological technique for increasing the level of biological fixation of air molecular nitrogen is the introduction of specific virulent, active strains of tubercle bacteria into the root zone. Symbiotic interaction between plants and nitrogen-fixing microorganisms is determined by the complementarity of macro- and micro-symbiont genes, species composition, virulence and activity of bacteria, air, water, temperature and nutrient regimes of soil, which determine the living conditions of both components of the symbiotic system and the course of the production process of grass peavine plants. The purpose of the research is to increase grass peavine productivity by op-timizing the mineral nutrition of plants in the fields. During the study it has been found that pre-sowing seed treatment with a complex of Rhizoline microbiological preparation (3.0 l/t) and Rhizoseyv bio-protector (1.0 l/t) against the background of N20R40K40mineral fertilization has a stimulating effect on the formation of the symbiotic apparatus of grass peavine plants. Increasing the level of applying mineral nitrogen has a negative effect on legume-rhizobial symbiosis, which is expressed in a decrease in the number of nodules and their mass. The combination of seed inoculation and foliar fertilization of plants in the branching phase Avangard R Bobovi with micro-fertilizer (2.0 l/ha) at the background of mineral fertilization favors the for-mation of powerful assimilation apparatus, prolongs the duration and productivity of its photosynthetic ac-tivity, increases the level of synthesized organic matter and increases plant productivity during its passing to the reproductive organs. In the agro-technological process of grass peavine cultivation, the most effective is the combination of pre-sowing seed inoculation with complex of Rizoline microbiological preparation (3.0 l/t), Rhizoseyv bio-protector (1.0 l/t) and foliar fertilization of plants with Avangard R Bobovi micro-fertilizer (2.0 l/ha) against the background of mineral fertilizers with a dose of active substance N40R40K40, which allows to increase the level of grain productivity of grass peavine areas to 3.07 t/ha.